Unbiased Screening of Kawasaki Disease Sera for Viral Antigen Exposure. (4th October 2017) - Quiat, Daniel; Kula, Tomasz; Shimizu, Chisato; Kanegaye, John T; Tremoulet, Adriana H; Pitkowsky, Zachary; Son, MaryBeth; Newburger, Jane; Elledge, Stephen; Burns, Jane C
Abstract: Background: Kawasaki disease(KD) is a medium-vessel vasculitis with a predilection for coronary arteries and is of unknown etiology. KD is responsible for the majority of acquired pediatric cardiovascular disease in the industrialized world, and is associated with development of coronary artery aneurysms in approximately 25% of untreated patients. Epidemiologic, pathologic, and clinical characteristics of KD display notable overlap with common pediatric viral illnesses, leading some to hypothesize that a viral infection is the inciting agent for KD. Methods: We investigated viral exposure history in KD patients by utilizing a recently developed technique to profile sera against the known human virome in an unbiased manner. We collected sera during the acute (pretreatment) and subacute phases of illness from 35 patients meeting clinical diagnostic criteria for KD, preferentially selecting patients with coronary involvement and/or late presentation. Control samples included healthy children and patients with known viral infections. Using phage immunoprecipitation sequencing(PhIP-seq), the sera were screened against a phage display library expressing epitopes that cover the complete reference protein sequences of the known 206 viruses with human tropism. Results: The mean patient age was 4.6 years(range 0.4–16.9) and mean day of illness at acute sample collection was 14.5 days(range 5 to 32). A majority of patients demonstrated coronary artery changes during the course of their illness(22/35, 62%). Sera from patients with KD demonstrated patterns of viral infection to common pediatric viruses with similar signal intensity and distribution to healthy control children. Interestingly, one patient demonstrated a strong signal to parvovirus B19. She presented on Illness Day 29 with periungual peeling and severe hip arthritis, and her initial KD course with 14 days of fever and 4/5 clinical criteria was missed. Conclusion: Although sera obtained early in the disease course could have missed a titer rise, we conclude that patients with KD do not exhibit unique serologic evidence of infection to known viruses or a viral exposure history that differs from age-similar healthy children. Disclosures: All authors: No reported disclosures.